2022
DOI: 10.6007/ijarbss/v12-i9/14712
|View full text |Cite
|
Sign up to set email alerts
|

A Confirmatory Factor Analysis on Teachers’ Sense of Efficacy Scale for In-Service Teachers in Malaysia

Abstract: This study presents the construct-related evidence of the Teachers' Sense of Efficacy Scale (TSES) developed by Tschannen-Moran and Woolfolk Hoy (2001) for in-service teachers in the Malaysian context. The under-researched validation of the TSES in the local context warranted an investigation into unrevealing the scale's psychometric properties. Thus, this cross-sectional study sought to determine the factor structure of the scale where factor loadings of each efficacy source contribution were determined. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…(3) teachers at different levels of education (i.e., basic, secondary) were merged for the validation. These characteristics of the sample can interact to provide a higher factor dimension (see Apablaza & Lira, 2016;Johar & Badrasawi, 2009;Pintus et al, 2021;Tsigilis et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(3) teachers at different levels of education (i.e., basic, secondary) were merged for the validation. These characteristics of the sample can interact to provide a higher factor dimension (see Apablaza & Lira, 2016;Johar & Badrasawi, 2009;Pintus et al, 2021;Tsigilis et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For studies that identified four‐ and five‐factor structures, three observations were made concerning the sample: (1) the teachers sampled had over 10 years of teaching experience; (2) the individuals sampled for the study were enrolled on innovative programs, which sought to train them for specialized skills; (3) teachers at different levels of education (i.e., basic, secondary) were merged for the validation. These characteristics of the sample can interact to provide a higher factor dimension (see Apablaza & Lira, 2016; Johar & Badrasawi, 2009; Pintus et al, 2021; Tsigilis et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations